Harnessing behavioral psychology to encourage individuals' adoption of pollinator conservation behaviors - Fair, Conor G.; Braman, S. Kris (Frontiers in Sustainable Cities, 2023)
The economic and ecological importance of pollinators and the increasingly evident declines of their populations has drawn concern from scientists, governments, and individuals alike. While research has focused on the ecological causes and solutions to pollinator declines, it is less understood how to motivate actual changes in behaviors to help conserve pollinators. Behavioral psychologists have developed many theories to explain how human behavioral drivers affect the adoption of pro-environmental behaviors such as recycling and other sustainability actions. A comprehensive model incorporating Norm Activation Theory, the New Ecological Paradigm, Values-Beliefs-Norm Theory, and the Theory of Planned Behavior suggests various psychological determinants that drive changes to pro-environmental behaviors. A survey using Qualtrics software was constructed to measure and analyze >1,500 individuals’ responses to questions designed to test the relationships between different types of pollinator conservation behaviors and the socio-psychological determinants of an individual’s intention to perform said behaviors. Previous behaviors, issue awareness, and positive attitudes towards pollinators consistently predict increased intention to perform pollinator conservation behaviors, which supports related research on pro-environmental behaviors. Other determinants like ascription of responsibility and perceived behavioral control had positive effects on the intention to perform some of the pollinator conservation behaviors tested. Understanding these relationships could help improve efforts to educate and increase adoption of these pollinator conservation behaviors. Lastly, many determinants had mixed and fewer significant relationships on the intention to perform conservations behaviors, which suggests the need for revisions of the specific wording of the survey tools and additional testing of these psychological determinants.